A model of community mobilization for the prevention of HIV in women and infants. Prevention of HIV in Women and Infants Demonstration Projects. - Person, B (1996)
The prevention of HIV in Women and Infants Demonstration Projects use a conceptual model for maximizing broad community participation for HIV prevention called the Community Mobilization Framework. The projects' comprehensive approach attempts to bring about changes on a community level using a model which encourages community-wide participation of persons with various roles and relationships in the community. The Community Mobilization Framework is one way to systematically conceptualize the organization of the community for the purpose of mobilizing the maximum number of community members around a common health initiative. A community becomes mobilized around an issue by endorsing health-enhancing attitudes, behaviors, and projects supporting positive health outcomes. This mobilization is expressed through the promotion, support, and delivery of motivational and informational health messages which convey consistent ideas, themes, and images. There are two fundamental bases of the Community Mobilization Framework. The first is its characterization of the variety of individual, social, and organizational roles and relationships in the community that might be used in a concerted campaign for HIV prevention for women. The second basis of the model is the description of the nature and extent of the involvement, which includes a continuum of involvement, ranging from simple endorsement to building active coalitions around a health initiative. The paper discusses practical methods of applying these principles, with the Women and Infants Demonstration Projects providing concrete examples.